Physico-Chemical and Bacteriological Quality of Water from Boreholes in Otuoke Community, Bayelsa State, Nigeria - V. Zige, Douye; J. Ogbolosingha, Atieme; D.T. Agboun, Temeweidoubra (Journal of Water, 2018)
The concern over exposure to drinking water contaminated and the resultant adverse effect on human health has prompted several studies evaluating the quality of drinking water sources. This study was carried out to determine the bacteriological and Physico-chemical qualities of commercial borehole water within Otuoke community in Bayelsa state Nigeria. Ten (10) water samples were collected from the various locations designated as (A-J). The Physico-chemical parameters were determined by using the photometric technique through the Colour Q photometer and the bacteriological analysis was determined by using aerobic plate method. The Physico-chemical parameters of the water samples analysed were within the acceptable limit of WHO standard of drinking water quality except for Bromine and cyanuric acid which ranged from 1.6±0.1 to 2.7±0.1 and 2±1 to 9±1 respectively. The Result of total bacteria count obtained from the borehole water samples ranged from 1.1 x 105cfu/ml to 6.9 x 105cfu/ml and there was no detected growth for the faecal coliform count of most of the samples except for BHW-I and BHW-J which had 1.3 x 104 to 7.9 x 104 respectively. Bacteria isolated and identified using conventional biochemical test include E. coli (17.9%), Klebsiella spp. (35.7%), Salmonella spp(25.0%), Enterobacter aerogenes (21.4%) The study therefore suggests that all the borehole water tested in Otuoke and environs are considered unsafe for consumption and therefore regular treatment before usage is recommended.
Keywords: Bacterial isolate; Physicochemical parameters; Borehole; water quality; Otuoke community.